Dispositional factors in adjustment among cadets of Nigerian military academy (2014)
Training outcomes of cadets in Nigerian military academy may be well determined by their adjustment capacity. The discouraging statistics of graduation rote (59%- 63% over a 5-year period) at the Nigerian Defence Academy reflect adjustment problem. This necessitated the need to investigate dispositional factors in adjustment of cadets in the Academy. The cross-sectional study was designed as a survey using questionnaires with scales for data collection. It involved a sample size of 63 drawn from cadets in their first to the fourth year (100L- 400L). The proposition that those who score higher on core self-evaluation will significantly report better adjustment than others was confirmed (t=10.9, df=61, p< 001). There was no significant difference in adjustment between cadets who attended military secondary schools and those from secular (civilian) secondary schools. It implied that self-esteem, emotional stability, generalized self-efficacy; and locus of control need to be considered in policy to prepare cadets to effectively cope in the academy. It was suggested that the current selection method which does not discriminate type of secondary school attended need to be a sustained policy. Finally, assessment of the dispositional factors in cadets during skill development programme would be necessary in order to adequately prepare them on the traits because they are significant factors in adjustment